Multiple Forms of Glucosephosphate Isomerase in Maize - Salamini, F. (1972)
Three apparently different glucosephosphate isomerases are found in the developing seeds of maize (Zea mays L.). Glucosephosphate isomerase I is found in both the endosperm and embryo. It is separable by column chromatography from glucosephosphate isomerase II of the developing endosperm and glucosephosphate isomerase III of the developing embryo and is further distinguished from them by heat stability, temperature activation, and relative insensitivity to the presence of zinc ions in the reaction mixture. Glucosephosphate isomerases II and III elute in the same fractions from diethylaminoethyl cellulose columns but are distinguished by electrophoretic mobility and reaction to the presence of adenosine 5′-triphosphate in the reaction mixture. All three isomerases give multiple banding patterns on electrophoresis. An extensive investigation of the conditions generating additional electrophoretic species and chromatographically separable minor activity peak (Ia) from glucosephosphate isomerase I has shown that these transformations are enhanced by dialysis, column chromatography, ammonium sulfate fractionation, and treatment with urea. The transformations are retarded by the presence of mercaptoethanol during these operations. We concluded that the multiple banding pattern seen on electrophoresis of glucosephosphate isomerase I prepared by certain procedures is artifactual. In germinating seeds of maize, glucosephosphate isomerases I and III are detectable, but II is not. It is possible that glucosephosphate isomerase II specifically catalyzes a step in starch biosynthesis.